Hubungan Kadar Komponen Besi Darah Pendonor terhadap Kualitas Packed Red Cells (PRC) di UDD PMI Provinsi Sumatera Selatan - Rahmi Widiyawati; Zen Hafy; Phey Liana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Iron is the essential component of our body especially used to make Hemoglobin. If the intake of iron enters from our food less than issued, it makes our reserve iron will be used, and it can cause iron deficiency. There are three pathogenesis stages of iron deficiency, first marked by reduced iron reserve or the absence of iron reserved, ferritin levels decreased, while other parameters to determinate the presence of iron deficiency( Serum Iron, TIBC, Hb, Transferrin Saturation) are still normal. The purpose of this study was to analyze the relationship level of donor iron components and quality of Packed Red Cells (PRC) in UDD PMI Provinsi Sumatera Selatan. This research is an analytic observational study with a cross-sectional design. The result of the research was conducted in April 2021, using 86 blood samples from donors. It showed there were 15 samples with iron deficiency. Consisted of 9 samples with iron deficiency in the first stage and 6 samples in the second stage. It is known that there are 6 samples with poor PRC quality; all of them are iron deficiency in the second stage. In conclusion, there is a significant relationship iron component level of the donor and the quality of PRC p<0,05.